Endoscopic mucosal electrodes: New directions for recording and regulating gastric myoelectric activity - Han, Xu; Zhu, Hong (Frontiers in Surgery, 2023)
With the gradual deepening of the study of gastric motility disorders, people increasingly realize that gastric myoelectric activity plays an important role in coordinating gastric function. This article introduces the advantages of endoscopic mucosal electrodes compared with traditional electrodes. Several different types of mucosal electrodes and how to fix the electrodes by endoscope are introduced. Endoscopic mucosal electrodes can record and regulate gastric myoelectric activity, which has great value in the study of gastric motility. Endoscopic mucosal electrode technique refers to the fixation of the electrode in the designated part of the gastric mucosa by endoscope. Through endoscopic mucosal electrodes, on the one hand, we can record gastric myoelectric activity, on the other hand, we can carry out gastric electrical stimulation to interfere with gastric rhythm. Endoscopic mucosal electrodes have higher accuracy than traditional cutaneous electrodes, less trauma and lower cost than serosal electrodes. Endoscopic mucosal electrodes have a good application prospect for diseases such as gastroparesis and obesity.